2012
DOI: 10.3390/pharmaceutics4030366
|View full text |Cite
|
Sign up to set email alerts
|

Using Ion-Selective Electrodes to Study the Drug Release from Porous Cellulose Matrices

Abstract: Polyvinyl chloride (PVC)-based solid-contact ion-selective electrodes (SC-ISEs), responding to propranolol hydrochloride (Pr+) and lidocaine hydrochloride (Ld+) cations as the model drugs with potassium tetrakis(4-chlorophenyl) borate (KTpClPB) as the ion exchanger, were studied. Different drug-polymer solutions were prepared with the model drugs, using different blend ratios of ethylcellulose (EC) and hydroxypropyl cellulose (HPC). Two different solid dosage forms were used. Polymer films were produced by sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 12 The detection limit achieved with the pencil lead based electrode is much better than the detection limit reported in the literature for PVC-based potentiometric solid-contact ion-selective electrodes (SC-ISEs) [45]. Compared with the detection of fluoxetine with a commercial BDD electrode, the capability of the double membrane coated pencil lead sensor is a unique advantage and enabled the measurements in tap and river water [31].…”
Section: Page 12 Of 32mentioning
confidence: 95%
“…A c c e p t e d M a n u s c r i p t 12 The detection limit achieved with the pencil lead based electrode is much better than the detection limit reported in the literature for PVC-based potentiometric solid-contact ion-selective electrodes (SC-ISEs) [45]. Compared with the detection of fluoxetine with a commercial BDD electrode, the capability of the double membrane coated pencil lead sensor is a unique advantage and enabled the measurements in tap and river water [31].…”
Section: Page 12 Of 32mentioning
confidence: 95%
“…14 The ophthalmic solution contains both LIG and FLS recommended for treatments that call for an anesthetic agent and a disclosure agent, including the Goldmann tonometry, measurement of intraocular pressure, gonioscopy, and other minor eye surgeries. 15 Many analytical techniques have been developed to quantify LIG, such as electrochemical methods, 1621 chromatographic methods, 2228 spectrophotometric methods, 2931 and FLS including, spectrofluorimetry method, 32 a chromatographic method, 33 and spectrophotometric method. 34 Meanwhile, no methods have been reported that can simultaneously quantify LIG and FLS in a co-formulated eye solution.…”
Section: Introductionmentioning
confidence: 99%
“…The literature comprises different analytical methods for the determination of LD some of which are: spectrophotometry , , HPLC , TLC , GC , CZE , voltammetry and ion selective electrode‐potentiometry . Simultaneous or selective determination of LD and DMA was reported using HPLC and TLC methods.…”
Section: Introductionmentioning
confidence: 99%